172k views
2 votes
Hi.Please its urgent
See image for question
Answer no 16 and 17

Hi.Please its urgent See image for question Answer no 16 and 17-example-1
User CWright
by
5.9k points

1 Answer

2 votes

9514 1404 393

Eexplanation:

16. Suppose the roots are α and kα. Then we can write the equation as ...

a(x -α)(x -kα) = 0

ax² -ax(α +kα) +akα² = 0

Comparing to the original equation, we can equate coefficients to get ...

  • b = -aα(1+k)
  • c = akα²

Solving the first for α gives ...

α = -b/(a(1+k)

Substituting into the second, we have ...

c = ak(-b/(a(1+k)))²

Multiplying by a(1+k)², we get ...

(1+k)²ac = kb²

Using k=2 gives ...

9ac = 2b² . . . . . as required

__

17. Using the previous result with k=1 (equal roots), we have ...

(1+k)²ac = kb²

4ac = b² . . . . . for k=1

______

Additional comment

We observed that the problems were similar, but had different factors relating the roots. So, we elected to solve the general case, then fill in the specific values for the two problems.

User Itaymendel
by
5.7k points